Stanniocalcin-1 in tumor immunity: acts via macrophages - Wang, Lele; Wang, Jianjun; Qiang, Weijie; Ge, Weihong (Frontiers in Immunology, 2024)
Tumor immune escape has become a research hotspot in the field of cancer immunotherapy. Tumor-associated macrophages (TAMs) are the key component of tumor microenvironment, which play a pivotal role in tumor immune escape by regulating the immunity checkpoints, inhibiting the activity of T lymphocytes and natural killer (NK) cells, and modulating proportion of different T cells. Stanniocalcin-1(STC1)is ubiquitously expressed in human body, which is proven to involve with tumor progression and clinical prognosis. Recently, STC1 is implicated in tumor microenvironment as a phagocytosis checkpoint, as well as regulates the immunity via macrophages. In the review, we discussed the role of STC1 and TAMs in tumor immunity and their crosstalk, hoping to provide references for the research of STC1 in tumor immunotherapy.